Effect of water conditions and nitrogen application on maize growth, carbon accumulation and metabolism of maize plant in subtropical regions. Issue 5 (16th April 2023) - Chi, Yu Xin; Gao, Fei; Muhammad, Ihsan; Huang, Jing Hua; Zhou, Xun Bo
ABSTRACT: Drought, water, and nitrogen (N) losses have always been great challenges for agricultural production in subtropical regions of China. To study appropriate irrigation regimes and reasonable N applications, a field experiment was conducted for summer maize ( Zea mays L.) from 2018 to 2019. Two irrigation treatments, namely, rain-fed irrigation and supplementary irrigation, were designed, and five levels of N fertilizer were applied. The differences in the growth periods of biomass, leaf area index, agronomic traits, carbon accumulation, and carbon metabolism enzyme activity were measured. Findings revealed that the interaction of water and N has a significant impact on maize growth. Compared to other N treatments, N250 produced significantly higher biomass, leaf area index, agronomic traits, carbon accumulation, and carbon metabolism enzyme activity. In 2018, the agronomic traits and leaf area index were significantly higher than in 2019. Meanwhile, additional irrigation could help improve agronomic traits and the leaf area index. Further correlation analysis revealed that carbon accumulation was positively correlated with carbon metabolism enzyme activity, although lower at maturity than in the flowering period. Overall, the findings suggest that supplementary irrigation in conjunction with N250 treatment is a worthwhile measure for sustainable maize production in subtropical regions of China.